Direct arylation (hetero-coupling) of heteroarenes via unsymmetrical palladium-PEPPSI-NHC type complexes. (1st November 2021) - Nawaz, Zahid; Gürbüz, Nevin; Naveed Zafar, Muhammad; Nawaz Tahir, Muhammad; Ashfaq, Muhammad; Karci, Hüseyin; Özdemir, İsmail
Graphical abstract: A series of ligands containing 1, 3-disubstituted benzimidazolium salts were synthesized from the corresponding precursors to form N -heterocyclic carbene (NHC). Furthermore, four new NHC-Pd-PEPPSI type complexes were synthesized from these ligands. The structures of all compounds have been characterized by 1 H NMR, 13 C NMR, and IR spectroscopy. All these newly synthesized complexes were found significantly active as catalysts toward direct arylation of five members heterocyclic compounds with arylbromide derivatives. Abstract: The growing interest of industry in the field of bi(hetero)arenes compounds, motivated us to synthesize these compounds via homogeneous catalytic route by using Pd PEPPSI-type complexes through direct arylation. In this work, the five new Pd PEPPSI-type complexes bearing NHC spectator ligands were synthesized and characterized by a bunch of spectroscopic techniques. Further confirmations of structural details were provided by a single-crystal X-ray diffraction study of one pro-ligand and one complex. All these newly synthesized Pd-carbene complexes were found significantly active as catalysts toward direct arylation of five members heterocyclic compounds such as n -propylthaizole, 2-acetylfurane and 2-acetylthiophene with aryl bromides derivatives. These catalysts give significantly good results within two hours with just 1 mol % catalyst loading.